THE PROBLEMS OF THE TRAINING SYSTEM OF SCIENTIFIC AND TEACHING STAFF IN POSTGRADUATE SCHOOL - S. Rukavishnikov (Гуманитарные и юридические исследования)
The article considers the main problems of the efficiency of the system of the preparation of scientific and scientific-teaching staff in contemporary conditions of the reformation of system of higher and postgraduate education in the Russian Federation. The integration into the Bologna process has the number of advantages, but became the reason of the series of objective difficulties, unavoidable under the conditions of the projecting of the European approach to higher education system on the existing post-soviet system. One of a such of difficulties is the reconsideration of the approach to the levels of higher and post-graduate education, which has significantly and disputable influenced to the efficiency of the current system of preparation of high-qualified staff. The establishment of the postgraduate school as another stage of higher education and the definition of the getting of a diploma of “researchist. teacher-researchist” as the main purpose of educational process instead the previous main purpose of the preparation and defense of a candidate’s dissertation means the significant change of postgraduate school’s priorities. It seems, that the educational component of this system has the secondary character, by primarily promoting the establishment of a postgraduate student in the role of a researchist, also including the preparation to the teaching process in a university. With that, the preparation of researchist as the high-qualified staff is highly demand not also within the framework of scientific and teaching community, but also in the system of the governing of the field of science and higher education, expert, legislative and other types of activity. And the most markable feature in the labor market is the presence of scientific degree in the relevant field of knowledge, but not the post-graduate school diploma, if the defense did not become the logical finish of study. The indicated problem requires the gradual, multi-stage reformation of the current legislation, which has to be focused to the correct prioritizing in the existing system of preparation of high-qualified staff, their careful selection and further stimulating.